1993
DOI: 10.1007/bf01694770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extrinsic positive end-expiratory pressure on mechanically ventilated patients with chronic obstructive pulmonary disease and dynamic hyperinflation

Abstract: The effects of PEEPe on iso-volume flow and hence on lung mechanics and hemodynamics, depend on many factors, such as airways resistances, lung volumes and airway characteristics, making the patient response to PEEPe unpredictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
8

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 26 publications
1
29
0
8
Order By: Relevance
“…The two V9/V curves were superimposed assuming that the end-inspiratory lung level was identical under both conditions, as indicated by a similar Ptr at the end of inspiratory occlusion. The presence of flow limitation was assessed by comparing expiratory V9 over a given portion of lung V [8,10,14]. If expiratory V9 was consistently higher when downstream P was lowered by removing the expiratory ventilator circuit or decreasing the PEEP level, the V portion was classified as being without flow limitation ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two V9/V curves were superimposed assuming that the end-inspiratory lung level was identical under both conditions, as indicated by a similar Ptr at the end of inspiratory occlusion. The presence of flow limitation was assessed by comparing expiratory V9 over a given portion of lung V [8,10,14]. If expiratory V9 was consistently higher when downstream P was lowered by removing the expiratory ventilator circuit or decreasing the PEEP level, the V portion was classified as being without flow limitation ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that mechanically-ventilated patients with ARDS may exhibit flow limitation during tidal expiration [8]. In which case the endotracheal tube resistance (Rtube), as well as the expiratory ventilator circuit, may not affect the expiratory flow and, thus, the rate of lung emptying [9,10]. It follows that calculating the ters without knowing if expiratory flow at the volume of interest is or is not limited might be misleading.…”
mentioning
confidence: 99%
“…Hence, inspiration begins at volumes at which the respiratory system exhibits a positive recoil pressure, referred to as intrinsic PEEP (PEEPi) [18][19][20][21][22]. This phenomenon is called dynamic hyperinflation and is a common finding in mechanically-ventilated patients [18][19][20][21].…”
Section: Missing Effortmentioning
confidence: 99%
“…In mechanically ventilated patients with chronic obstructive pulmonary disease (COPD), the effect of PEEP on DRrs has also been studied. In one study, by experimental design, the maximal applied PEEP was limited to 86% of the intrinsic PEEP [6]. Under the latter conditions, the changes in end-expiratory lung volume (EELV) were necessarily very small (mean of 0.13 L), and accordingly in that study, there was little or no change of DRrs and Rint,rs.…”
mentioning
confidence: 98%